Sindrom Kardiovaskular-Ginjal-Metabolik: Konsep Terkini untuk Klinisi - Yamin, Muhammad; Putra, Harits Adi (UI Scholars Hub, 2024)
Cardiovascular-kidney-metabolic (CKM) syndrome is a systemic abnormality resulting from complex pathophysiological interactions among cardiovascular disease, chronic kidney disease, and metabolic risk factors, particularly diabetes mellitus and obesity. In clinical practice, the management of CKM syndrome encounters some significant challenges, including the lack of clinicians’ knowledge regarding the most up-to-date therapy, limited drug availability, and restrictions on health insurance. Those issues potentially lead to a rise in morbidity and mortality rates of patients with CKM syndrome. This article elucidates the most updated concept of CKM syndrome regarding its pathophysiology, diagnostic approach, and treatment based on clinical stages ranging from stage 0 to stage 4. Some emerging medications have proven to improve the prognosis of patients with CKM syndrome by targeting any of the pathophysiological interactions, namely sodium-glucose cotransporter-2 inhibitors, glucagon-like peptide-1 receptor agonists, angiotensin-enzyme converting inhibitors, and angiotensin receptor blockers. Recent studies have proven their efficacy in reducing hospitalisation rates and cardiovascular-related mortality. Not only by applying current clinical guidelines in practice, CKM syndrome should also be managed holistically in a multidiscipline manner starting from health promotion to curative treatment. Hence, the current concept of CKM syndrome pointing to holistic and multidiscipline management hopefully could prevent the progressivity of the disease and reduce the morbidity and mortality rates.